The Feminine and the Masculine in Roman de Silence - Valentina S. Sergeeva (Studia Litterarum)
This article examines the medieval French novel Roman de Silence in the context of gender ambiguity of its protagonist. The first part studies the novel’s connection to the broader tradition of “strong women” (mulier fortis) literature and defines its place within the context of the function and reception of women-warriors in the medieval society. The second part explores the authors’ individual, intratextual authorial attitude to the story (taking into account that “master Heldris,” the author of Roman de Silence, could have been a woman hiding her sex behind the male nome de plume). In particular, it focuses on “the grammar of sexes” and the self-consciousness of the protagonist doing something socially inappropriate and yet, at the end, behaves more righteously than other, “conventional” characters. Without giving any definite judgment, the author of Roman de Silence discusses the importance of Nature and Education in shaping one’s personality and weighs the merits and the shortcomings of rules and social expectations that determine every man’s and woman’s life in society. In fact, the happy ending of the novel (the main heroine who does not have to hide her sex any more, marries the king) does not put an end to the discussion of the gender question; the author still proposes to test it one more time and, if necessary, debunk traditional gender roles and attitudes.